Harvesting, honey extraction and packaging - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
Careful harvesting of honey using the right equipment, plus extraction, filtering and packaging of honey.